1982
DOI: 10.1128/iai.35.2.546-551.1982
|View full text |Cite
|
Sign up to set email alerts
|

Genetics of murine resistance to Trypanosoma cruzi

Abstract: Resistance to the protozoan parasite Trypanosoma cruzi is governed by multiple genetic factors, including at least one coded for by a locus in or neat the major histocompatibility complex of the mouse. The influence of the H-2 locus on resistance was evident when H-2 congenic mice on a strain background of intermediate resistance were challenged or when the survival of H-2 typed F2 mice was followed. The H-2k haplotype of the susceptible C3H/An strain was associated with higher mortality when compared with the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
19
0
4

Year Published

1984
1984
2005
2005

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 77 publications
(26 citation statements)
references
References 20 publications
3
19
0
4
Order By: Relevance
“…Several models of T. cruzi infection exist, employing various strains of mice and parasites, and these exhibit differences in parasite tropism of cells and development of disease, particularly in relation to host sex and age [28,29]. We detected the highest tissue parasite burden in the spleen.…”
Section: Discussionmentioning
confidence: 71%
“…Several models of T. cruzi infection exist, employing various strains of mice and parasites, and these exhibit differences in parasite tropism of cells and development of disease, particularly in relation to host sex and age [28,29]. We detected the highest tissue parasite burden in the spleen.…”
Section: Discussionmentioning
confidence: 71%
“…Murine studies have demonstrated that host genetics may influence resistance to acute infection. Yet, only a few studies haveexamined the role of host genes in regulating survival, and among these studies conflicting results have been reported (Trischmann et al 1978, Trischmann & Bloom 1982, Wrightsman, Krassner & Watson 1982, Trischmann 1983, Wrightsman et al 1984, Juri, Ferreira, Ramos & Hoecker, 1990.…”
Section: Introductionmentioning
confidence: 99%
“…Infection may also lead to acute disease with fatal outcome or, more commonly, the development of chronic disease with severe associated pathologies. In mice, different inbred strains may develop fatal or very mild infections when inoculated with the same T. cruzi isolate (1,2). Similarly, different T. cruzi isolates produce variable courses of infection within a given mouse strain (3).…”
mentioning
confidence: 99%